Bacteria and diatom co‐occurrence patterns in microbial mats from polar desert streams. (24th September 2012) - Stanish, Lee F.; O'Neill, Sean P.; Gonzalez, Antonio; Legg, Teresa M.; Knelman, Joseph; McKnight, Diane M.; Spaulding, Sarah; Nemergut, Diana R.
Summary The ephemeral stream habitats of the McMurdo Dry Valleys of Antarctica support desiccation and freeze‐tolerant microbial mats that are hot spots of primary productivity in an otherwise inhospitable environment. The ecological processes that structure bacterial communities in this harsh environment are not known; however, insights from diatom community ecology may prove to be informative. We examined the relationships between diatoms and bacteria at the community and taxon levels. The diversity and community structure of stream microbial mats were characterized using high‐throughput pyrosequencing for bacteria and morphological identification for diatoms. We found significant relationships between diatom communities and the communities of cyanobacteria and heterotrophic bacteria, and co‐occurrence analysis identified numerous correlations between the relative abundances of individual diatom and bacterial taxa, which may result from species interactions. Additionally, the strength of correlations between heterotrophic bacteria and diatoms varied along a hydrologic gradient, indicating that flow regime may influence the overall community structure. Phylogenetic consistency in the co‐occurrence patterns suggests that the associations are ecologically relevant. Despite these community‐ and taxon‐level relationships, diatom and bacterial alpha diversity were inversely correlated, which may highlight a fundamental difference between the processes that influence bacterial and diatom community assembly in these streams. Our results therefore demonstrate that the relationships between diatoms and bacteria are complex and may result from species interactions as well as niche‐specific processes.